2016
DOI: 10.1016/j.jimonfin.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy spillovers and the trilemma in the new normal: Periphery country sensitivity to core country conditions

Abstract: for sharing the shadow interest rate data. An earlier version of this paper circulated as "Analysis on the Determinants of Sensitivity to the Center Economies." All remaining errors are ours. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(39 citation statements)
references
References 27 publications
2
27
0
1
Order By: Relevance
“…Notice that this literature has not claimed that base-country monetary policy does not impact at all local monetary policy in economies with flexible exchange rates, but rather that the effects are weaker compared to economies with less flexible exchange rates. A number of recent studies has confirmed the findings of this strand of the literature, including Obstfeld (2015), Caceres et al (2016), Kharroubi and Zampolli (2016), Ricci and Shi (2016), Obstfeld et al (2017), as well as Aizenman et al (2016). This paper is also related to the literature arguing that the trilemma has morphed into a dilemma.…”
Section: Existing Literaturesupporting
confidence: 72%
“…Notice that this literature has not claimed that base-country monetary policy does not impact at all local monetary policy in economies with flexible exchange rates, but rather that the effects are weaker compared to economies with less flexible exchange rates. A number of recent studies has confirmed the findings of this strand of the literature, including Obstfeld (2015), Caceres et al (2016), Kharroubi and Zampolli (2016), Ricci and Shi (2016), Obstfeld et al (2017), as well as Aizenman et al (2016). This paper is also related to the literature arguing that the trilemma has morphed into a dilemma.…”
Section: Existing Literaturesupporting
confidence: 72%
“…Increased capital account openness has come at the cost of reducing the independence of monetary policy or limiting ER. Aizenman, Chinn, & Ito (2016) suggests that exchange rate market pressures in peripheral economies are sensitive to movements in the exchange rate of the central economy during and after the global financial crisis. Open macro policy settings, especially exchange rate regimes, also have an indirect effect on the strength of financial relations, interacting with other macroeconomic conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…15 Latvia is included as an emerging economy in our regression as defined as such by the IMF except in 2003-2005. We do not exclude Latvia and Lithuania from the sample because they only joined the euro zone in 2014 and 2015, respectively, and only after resolution of the European sovereign debt crisis. 16 Aizenman et al (2016) also set the GFC period from 2007:Q3 to 2009:Q3, while Ahmed and Zlate (2014) exclude the crisis period from 2008:Q3 to 2009:Q2 in their estimation. 17 According to the results of a correlation test, there is no significant correlation between any of the explanatory variables.…”
Section: Inoguchimentioning
confidence: 99%